Promotive Health Interventions Through Environmental Sanitation and Water Quality Education for Diarrhea Prevention Among Children in the Medan Sunggal Community Health Center Area - Fauziah, Dinda; Ginting, Chrismis Novalinda; Nasution, Sri Wahyuni (Riviera Publishing, 2026)
This study aims to assess the effectiveness of promotive health interventions through environmental sanitation and water quality education for diarrhea prevention among children in the Medan Sunggal Community Health Center area on the knowledge and practices of PHBS among families with toddlers, as well as its relationship with the incidence of diarrhea in toddlers in the working area of the Medan Sunggal Health Center. The study used a quasi-experimental design with a one-group pretest–posttest approach involving 50 families with toddlers selected purposively. Interventions in the form of environmental sanitation and water quality education were provided through structured counseling. Data analysis was conducted using the Wilcoxon signed-rank test and the chi-square test. The results showed a significant increase in maternal knowledge of PHBS after the intervention (p < 0.001), while the increase in maternal PHBS practices was not statistically significant (p = 0.073), although descriptively it improved. The chi-square test analysis indicated no significant relationship between maternal knowledge and the incidence of diarrhea (p = 0.529) or between maternal PHBS practices and diarrhea incidence (p = 0.636). These findings suggest that educational interventions effectively improve cognitive aspects but are insufficient to reduce diarrhea incidence without improvements in physical environmental factors. Environmental sanitation and water quality education increase mothers’ knowledge of Clean and Healthy Living Behaviors; however, they alone are inadequate to reduce diarrhea incidence in toddlers, as factors such as access to clean water, proper sanitation facilities, and environmental hygiene also play a critical role.